1991
DOI: 10.1182/blood.v77.10.2109.bloodjournal77102109
|View full text |Cite
|
Sign up to set email alerts
|

Combined therapy with recombinant granulocyte colony-stimulating factor and erythropoietin decreases hematologic toxicity from zidovudine

Abstract: Twenty-two patients with acquired immunodeficiency syndrome (AIDS) or severe AIDS-related complex and multilineage hematopoietic defects were treated with recombinant granulocyte colony-stimulating factor (G-CSF) and erythropoietin (EPO) in a phase I/II trial. All patients were neutropenic and anemic after withdrawal of all bone marrow-suppressive drugs. Daily, G-CSF was subcutaneously self-administered until an absolute neutrophil count (ANC) greater than 6,000/microL was achieved and maintained for 2 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Neutropenia is common in patients with advanced HIV infection. The cause vary, but neutropenia is often caused by the use of myelotoxic agents directed against HIV, myelosuppressive chemotherapy, or radiation therapy [1,2,4,25]. G-CSF is known to increase the absolute neutrophil count by stimulating proliferation and differentiation of neutrophil precursors including CD34 progenitor cells [25±27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutropenia is common in patients with advanced HIV infection. The cause vary, but neutropenia is often caused by the use of myelotoxic agents directed against HIV, myelosuppressive chemotherapy, or radiation therapy [1,2,4,25]. G-CSF is known to increase the absolute neutrophil count by stimulating proliferation and differentiation of neutrophil precursors including CD34 progenitor cells [25±27].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the CD4 count in HIV-infected patients treated with G-CSF increase as well [1±3, 9, 11±13], and in one study an increase in the number of naive CD4 cells was found [9]. In addition, short-term G-CSF administration may partially restore the in vitro interleukin (IL)-2 production and lymphocyte proliferative response in blood from HIV-infected patients [1,14], although one study has shown a decrease in these functions [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, less than the recommended dosage in HIV-infected patients may result in an adequate response. 16 Dosages of G-CSF were titrated to maintain a nadir ANC of 500-1500 cells/mm 3 in patients with HIV who had dose-limiting neutropenia due to ganciclovir. 8 All seven patients were maintained with the recommended dosage of ganciclovir and required only one to three doses of G-CSF/week.…”
Section: (Pharmacotherapy 1999;19(3):356-362)mentioning
confidence: 99%